Using Awl To Improve The Academic Vocabulary Mastery At The Second Semester Students Of Universitas Bhinneka PGRI - Ika Rakhmawati; Yulia Nugrahini (Journal of Innovative and Creativity, 2025)
One of the most crucial components of language proficiency is academic vocabulary development, thus it is crucial to concentrate on this when learning English. However, depending on their requirements and educational level, children may also build their vocabulary on their own as they go through life. One of the language abilities that should be taught and acquired is academic vocabulary. Without mastering a particular amount of vocabulary, it is indisputable that learning a language will be difficult. Without a large vocabulary, a language learner cannot effectively convey or articulate their thoughts both orally and in writing (Folse, 2011; Dehham, 2021). Vocabulary development is essential to any language learning process, especially when it comes to introducing and reinforcing new lexical elements. According to the aforementioned argument, words and vocabulary are constantly connected. The process of learning a language involves being familiar with the vocabulary, understanding its meaning, and using it in sentences. Based on the students’ score on preliminary study, it is shown that the students’ academic vocabulary mastery needed improvement caused their scores were low. There were 59% of 22 students who passed the writing ability test. The success of this class was less than 80%. The result could not achieve the criteria of success. It means that the students’ academic vocabulary mastery before the implementation of the strategy is quite weak. To improve the students’ academic vocabulary mastery, the researcher did this classroom action research. From first cycle, it is known that amount of the students who passed the writing test increased. The result of the study on this cycle was 16 students passed the writing test. 73% of the students were successful. The result of second cycle was 20 students passed the Academic Vocabulary test. 91% of the students were successful